Glass transition and degree of conversion of a light-cured orthodontic composite - Sostena, Michela M. D. S. [UNESP]; Nogueira, Renata A. [UNESP]; Grandini, Carlos Roberto [UNESP]; Moraes, João Carlos Silos [UNESP] (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2009)
Objective: This study evaluated the glass transition temperature (T(g)) and degree of conversion (DC) of a light-cured (Fill Magic) versus a chemically cured (Concise) orthodontic composite. Material and Methods: Anelastic relaxation spectroscopy was used for the first time to determine the T(g) of a dental composite, while the DC was evaluated by infrared spectroscopy. The light-cured composite specimens were irradiated with a commercial LED light-curing unit using different exposure times (40, 90 and 120 s). Results: Fill Magic presented lower T(g) than Concise (35-84 degrees C versus 135 degrees C), but reached a higher DC. Conclusions: The results of this study suggest that Fill Magic has lower T(g) than Concise due to its higher organic phase content, and that when this light-cured composite is used to bond orthodontic brackets, a minimum energy density of 7.8 J/cm(2) is necessary to reach adequate conversion level and obtain satisfactory adhesion.
Keywords: Orthodontic composite; Glass transition temperature; Degree of conversion; Mechanical spectroscopy; Infra-red spectroscopy